Relationship Among Happiness, Life Satisfaction and Resilience in University Students - Fauzia Malik, Saima Sajjad (PJE, 2023)
The present study seeks to explain the interactive and relative effects of happiness, life satisfaction and resilience among university students in Pakistan. Basic objective of this research was to find out the relationship between happiness, life satisfaction and resilience, further to investigate the level of resilience, happiness and life satisfaction among male and female students. Disproportionate stratified sampling technique was used to select 400 university students (male=200, female=200) from the universities of Rawalpindi and Islamabad. The study was conducted in two phases. In phase-I pilot study was conducted and in phase-II main study was administered. The data for the study was collected through stratified random sampling technique and three reliable instrument used were; Oxford Happiness Scale (1990), Life satisfaction scale (1985) and Resilience Scale (1993). Data was analyzed using statistical techniques like Pearson correlation; Independent sample t-test was used. Results of the study indicated a significant inverse relationship between the variables of resilience and happiness (r=-.472**) where female students were happier than male students (M + SD= 109.8442 + 15.45855) and a significant inverse relationship between life satisfaction and resilience (r=-.112* ) among male and female university students. The results also indicated that females are more satisfied with life than males (M + SD= 23.3810 + 5.64858). It was also found that there were significant gender differences in university student’s scores on resilience scale (M + SD= 79.4201 + 26.55817). Males were found to be more resilient than females. The findings of the present study have implications for students’ counseling, awareness and therapy. It was recommended that the training of the students should also be done so that they deal with life events and circumstances effectively while maintaining their psychological health.